'In Aid of Bangladesh': The Soft Power Push by Bombay's Civil Society Towards the Liberation of East Pakistan. (September 2022) - Tiwary, Bipin K.; Roy, Anubhav
India's all-out war with Pakistan for the liberation of Bangladesh in 1971 may have been brief, but it came after a lengthy prelude. For months, New Delhi laboured to convince the world—especially the West—about the grim consequences of Islamabad's oppressive bid to stomp out Bengali nationalism in East Pakistan. While there is adequate literature chronicling the diplomatic persuasion undertaken by India leading up to the war of 1971 and its military pursuits during the conflict, the academic interest in the civil society's contribution to the cause appears insufficient. A dearth of retrospective case studies of India's socio-cultural responses to its foreign affairs is, in fact, noticeable, especially in the discourse on Indian soft power. In an attempt to address this gap, by principally relying on the historical evaluative analysis of primary news reports, this article attempts to chronicle the contributions towards the cause of East Pakistan's liberation by individual and collective civil society actors of Bombay (now Mumbai)—a cultural and commercial hub of India—focusing on the efforts of a dedicated volunteer-run committee for fundraising, the fraternity of the city's Bollywood celebrities, and a few distinguishable films produced within it. In doing so, the potential of these actors to qualify as resources of India's soft power during that tense year is also examined.